Fifth Amendment Consolidation Of The 1945 Constitution Of The Republic Of Indonesia - Ansor Ansor (NOMOI Law Review, 2020)
Consolidation is an action taken to strengthen, unite and strengthen the relationship of national unity and unity if it is associated with the fifth amendment of the 1945 Constitution of the Republic of Indonesia. The question that the author discusses in this study first is the desire of the authorities to make the fifth amendment to the 1945 Constitution of the Republic of Indonesia through consolidation? As for the conclusion of this study that in the framework of the Consolidation of the Fifth Amendment of the 1945 Constitution of the Republic of Indonesia will bring the Indonesian people to a better and orderly future and there will be no more cracks and consolidation will be realized in accordance with the rules of developed and modern countries such as the United States of America as a comparison. The method used in this study is a normative juridical legal research method. The fifth amendment is able to be the basis of national consolidation, because the state actors agree that the 1945 Constitution of the State of the Republic of Indonesia is used as the Grund Norm, will be able to bring prosperity to the nation and state, with this fifth amendment able to bring and develop an Indonesian state that consists of various kinds ethnicity, religion, race and culture.Keywords: Consolidation , Amendment, Constitution, Presidential System.